Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve the system using the substitution method. y = -5x – 13 6x + 6y = -6 please help me NO LINKS!


Sagot :

Answer:

Step-by-step explanation:

y=-5x-13

Since we know the value of y we can substitute it in

6x+6(-5x-13)=-6

6x-30x-78=-6

-24x=72

-x=3

x=-3

Now that we know the value of x we can solve Y

y=-5(-3)-13

y=15-13

y=2